Open and distance learning (ODL): Traditional or frugal innovation? - Marcelo Tsuguio Okano; Henry de Castro Lobo dos Santos; Edson Luiz Ursini; Marcelo Eloy Fernandes; Jaqueline Geisa Cunha Gomes; Cristina Blanco González-Tejero; Sorin Gavrila Gavrila (Contemporary Economics, 2023)
New information and communication technologies (ICTs) are contributing to the advancement and popularization of distance learning, and its use by educational institutions is accelerating. Some characteristics of distance learning are remarkable, such as its quantity, scalability, ability to serve many students at the same time, scope, lower costs, and so on. Some of these characteristics refer to a type of innovation called frugal, which is the ability to "do better with fewer resources for more people", that is, create significantly more value and minimize the use of resources. The objective of this research was to analyze the characteristics of distance learning through the theoretical lens of frugal innovation using the conceptual model of frugal innovation. The characteristics listed in the Rossetto model were researched qualitatively and quantitatively to obtain a solid conclusion, as this model uses a scale to identify and measure frugal innovation. The Rossetto model was developed and tested using the results of five collections of data from three different countries (Brazil, the United States of America, and India), with the entire development and refinement processes being subjected to an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). The final validation of the scale was based on data from 1130 companies. The mixed (qualitative and quantitative) methodological procedures were used to analyze the data obtained from the field research. The qualitative analysis consisted of verifying the characteristics of frugal innovation through Rossetto's conceptual model, and exploratory factor analysis was chosen for the quantitative analysis. Ten of the characteristics of the model sought, analyzed in three dimensions, identified, and strongly indicated that ODL can be considered as a frugal innovation, convincing and confirming that ODL has as main characteristics of the FI such as cost reduction, focus on essential functionalities and improved performance in relation to face-to-face teaching and thus, highlighting that the main value created is to do better with fewer resources than traditional teaching for a greater number of students served.
Keywords: O33; 330; open and distance education; ODL; AFE; frugal innovation